Iron(III) Chloride Promoted Cyclization: A Facile Approach to Polycyclic Aromatics for Functional Materials - Cao, Yue; Wang, Xiao-Ye; Wang, Jie-Yu; Pei, Jian (Synlett, 2014)
Polycyclic aromatics have attracted much research interest owing to their promising applications in supramolecular chemistry and organic electronics. Much research focuses on developing novel polycyclic aromatics with diverse properties. Among various synthetic methodologies for constructing polycyclic aromatics, iron(III) chloride (FeCl3) promoted cyclization has been extensively utilized in the synthesis of such organic π-conjugated materials. In this account, we summarize investigations of the FeCl3-promoted cyclization reaction, the construction of a series of polycyclic aromatics through this method, and the applications of such compounds in thin-film transistors and functional nanomaterials and nanodevices.1 Introduction2 Synthetic Considerations3 Sulfur-Containing Heteroarenes for Thin-Film Transistors4 Large Heteroarenes for Nanomaterials and Nanodevices5 Summary and Outlook
Keywords: polycycles; heterocycles; ring-fused systems; self-assembly; supramolecular chemistry